TsumatoBin / Nur Illiyana Zolkefli ... [et al.] - Zolkefli, Nur Illiyana; Zamri, Nursafura Basyira; Sukor, Nur Fatihah; Ramli, Nur Atikah Syahirah; Yaakob, Hazirah; Ismail, Izyan Zarifah; Nizam, Nur Azmina (2022)
Green Lux is a supplier company that distributes a very efficient, of useful and affordable products. It produces a 2in1 trash bin that combines the trash can with a food composter that helps life get easier, named TsumatoBin. It allowed people to have a pleasant living environment by reducing bad odors from rubbish without facing any problems such as hard- to-tie-up plastic bags, small space, and uncontrol food waste. This product has advanced technology function with affordable price that can attract customers to own it. We aim to market our product with the cost of RM1,616.00 per unit. The advantages of our product are easy to put anywhere since the size is not too big and saves space. This product is indeed efficient to the customers as it helps to tie up the plastic bag. Besides reducing bad odors, this product can also produce organic fertilizer from the food composter partthat the process only takes a few hours to finish. It is free from any chemical agents that have a toxic effect on human health, plants, and animals. Our target market is mainly everyone in Negeri Sembilan who values cleanliness and prefers a pleasant living environment such as households, students, and more. Based on our price, we aim to market our product to M40 and T20 people from all races and range between 20 to 55 years old. Based on their monthly income, they can afford to have our product, TsumatoBin for their own. Another alternative to expand our business, we also focus on online market platforms. We choose platforms such as Shopee and Lazada to further diversify our product to easily to purchase by all the customers.